2009
DOI: 10.1063/1.3053568
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aluminum nanoparticle surface treatment on the electrical properties of polyethylene composites

Abstract: In this study, we investigated the influence of the surface treatment of Al nanoparticles on the electrical properties of linear low density polyethylene composites. Octyl-trimethoxysilane was used as a nonpolar silane coupling agent for the surface treatment of Al nanoparticles. It was found that the incorporation of nonpolar octyl groups onto the surface of Al nanoparticles not only increased the percolation threshold and the resistivity but also improved the dielectric properties as compared to the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…Detailed chemical characterization of coated nanoparticle surfaces was described in elsewhere. 7,10 It has been found that $ 1 wt % of OTMS silane coupling agent covalently bonded to the Al surface and that the surfaces of the OTMS coated nanoparticles were more hydrophobic when compared with the surfaces of the as received nanoparticles because of the introduction of non-polar octyl groups on the surfaces. The schematic of surface characteristics for a silane treated Al nanoparticle is presented in Figure 4.…”
Section: Effects Of Dispersion Of Nanoparticles and Interfacial Adhesmentioning
confidence: 99%
“…Detailed chemical characterization of coated nanoparticle surfaces was described in elsewhere. 7,10 It has been found that $ 1 wt % of OTMS silane coupling agent covalently bonded to the Al surface and that the surfaces of the OTMS coated nanoparticles were more hydrophobic when compared with the surfaces of the as received nanoparticles because of the introduction of non-polar octyl groups on the surfaces. The schematic of surface characteristics for a silane treated Al nanoparticle is presented in Figure 4.…”
Section: Effects Of Dispersion Of Nanoparticles and Interfacial Adhesmentioning
confidence: 99%
“…Materials with high dielectric constant are expected to play increasingly important roles in many applications such as electric stress control [1], electric energy storage [2] and actuators [3]. Compared with inorganic ceramics, high dielectric constant polymer nanocomposites have attracted ever-increasing attention due to their easy-processing and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…One classic approach is to introduce either high dielectric constant ceramic particles (i.e., Barium titanate, Cadmium oxide, Tungstic oxide) [6,10,[11][12][13][14][15][16] or high electric conductivity particles such as metal (i.e., Aurum, Silver, Copper, Aluminum) [2,[17][18][19][20][21][22][23] and carbon fillers [24][25][26][27][28][29][30] into a polymer. To date, two technical routes have been developed to achieve high dielectric constants polymer composites, i.e., the preparation of percolative composites and ceramic/polymer composites [5].…”
Section: Introductionmentioning
confidence: 99%